Parental Challenges in Promoting the Well-being of Talented Youths in Indonesia: A Phenomenological Study - Nur Setiawati Dewi; Piyanuch Jittanoon; Wantanee Wiroonpanich (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Parenting talented youths is a challenging task since most talented youths experience role complexities in their lives. Thus, raising talented youths can lead to increased challenges of parenting.Purpose: This study aimed to explore the challenges faced by Javanese Muslim parents in promoting the well-being of talented youths.Methods: A descriptive phenomenological approach was chosen to guide this study. Thirteen Javanese Muslim parents of talented youth (nine men and three women) were recruited using snowball and purposive sampling techniques. The data were obtained by conducting semi-structured interviews and field notes. The collected data were transcribed using verbatim transcription and analyzed using Giorgi’s method of analysis.Results: Three themes were found after data analysis, i.e., challenges coming from the youths, challenges from the community, and the existence of financial constraints in the family. Challenges coming from the youth were related to the oppositional behavior of talented youths and difficulties in managing children’s activities as students and as talented youths. Challenges from the community included low commitment and belittling behavior from teachers or lecturers, ridicule from their neighbors, gender-based discrimination, and the absence of support from the organization. Another theme was related to financial constraints in the family which made it difficult for parents to finance their youth’s education and talent activities.Conclusion: Identifying the actual problems experienced by the talented youths’ parents could help nurses develop appropriate family programs, consider, and incorporate holistic aspects into the programs to obtain optimal results.